Histamine receptors on guinea-pig alveolar macrophages: Chemical specificity and the effects of H1- and H2-receptor agonists and antagonists - Diaz, Patricia (1979)
Various guinea-pig leucocytes were tested for their capacity to bind histamine coupled as a rabbit serum albumin conjugate (H-RSA) to formalised ox red cells. The percentage of rosette-forming target cells was directly related to the concentration of erythrocyte-bound H-RSA. Under optimal experimental conditions the numbers of rosettes varied from 60 to 81% for alveolar macrophages, 14 to 73% for peritoneal macrophages, 14 to 30% for blood monocytes, 27 to 48% for lymph node cells, 7 to 24% for blood lymphocytes and 0 to 29% for peritoneal and blood neutrophils. Virtually no histamine rosettes were formed with eosinophils or basophils. Free histamine partially inhibited rosette formation by alveolar macrophages in a dose-dependent fashion from 10(−3) to 10(−5) mol/l, and complete inhibition was achieved by the H-RSA conjugate. In contrast, amines closely related to histamine such as L-histidine and the major histamine catabolites, imidazoleacetic acid, 1,4-methylhistamine, l-methyl-4-imidazoleacetic acid and N-acetylhistamine, had no inhibitory effect. The histamine H1–receptor antagonists, mepyramine and chlorpheniramine, and the H1-receptor agonist, 2– (2–aminoethyl) thiazole, all inhibited rosette formation by alveolar macrophages in a dose-dependent fashion. However, the H2-receptor antagonists, burimamide and metiamide, and the H2-receptor agonists, Dimaprit and 4–methyl–histamine, were inactive. These experiments suggest that (1) compared to other leucocytes, histamine receptors are particularly well expressed on the alveolar macrophage, (2) these receptors have a high degree of specificity for histamine in that other amines, closely related chemically, did not inhibit rosette formation, and (3) the binding of histamine to the alveolar macrophage membrane is H1- and not H2- receptor dependent.